The Ethics Of Pharmacogenomic Testing In Community Pharmacy (Journal of Namibian Studies : History Politics Culture, 2022)
Health care providers have traditionally provided individualized, patient-centered treatment plans to their patients; yet, the special significance that a patient's genetic profile plays in determining the success or failure of therapy has received little attention. Terms like precision medicine, personalized medicine, and pharmacogenomics (PGx) have generated discussion in the scientific and medical sectors due to recent improvements in the understanding and implementation of genetic-based care. Pharmacogenomics is the study of how an individual's genetic makeup affects how they react to pharmaceutical treatments. Applications of pharmacogenomics are numerous in clinical specializations and human health domains. This study is to investigate some of the most important ethical issues surrounding pharmacogenomic testing in community pharmacies as well as patient views regarding the practice.